2012
DOI: 10.1186/1297-9716-43-70
|View full text |Cite
|
Sign up to set email alerts
|

The search for the gene mutations underlying enterotoxigenic Escherichia coli F4ab/ac susceptibility in pigs: a review

Abstract: Diarrhoea due to enterotoxigenic Escherichia coli with fimbriae F4 (ETEC-F4) is an important problem in neonatal and just weaned piglets and hence for the pig farming industry. There is substantial evidence for a genetic basis for susceptibility to ETEC-F4 since not all piglets suffer from diarrhoea after an ETEC-F4 infection. It is assumed that the wild boar was originally ETEC-F4 resistant and that susceptibility towards ETEC arose after domestication. There are different phenotypes in the pig determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…usceptibility to enterotoxigenic Escherichia coli (ETEC) expressing the F4 fimbriae, mainly F4ab and F4ac, is dominantly inherited in neonatal and postweaning piglets (1). ETEC-related postweaning diarrhea (PWD) in piglets is an important cause of economic losses in swine farming (2).…”
mentioning
confidence: 99%
“…usceptibility to enterotoxigenic Escherichia coli (ETEC) expressing the F4 fimbriae, mainly F4ab and F4ac, is dominantly inherited in neonatal and postweaning piglets (1). ETEC-related postweaning diarrhea (PWD) in piglets is an important cause of economic losses in swine farming (2).…”
mentioning
confidence: 99%
“…A (Python et al, 2005;Yan et al, 2009;Schroyen et al, 2012). Ren et al (2012) showed evidence that MUC13 is a good candidate for the F4ac receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The two variants of the fimbriae F18 bind to the same host receptor, whereas the three F4 variants F4ab, F4ac and F4ad each exhibit a specific binding pattern including variation in binding strength (Bijlsma et al, 1982;Billey et al, 1998). The fully adhesive receptor(s) for F4ab and F4ac is/are either controlled by one gene (F4bcR) or by two closely linked genes (Python et al, 2005;Yan et al, 2009;Schroyen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This fact gives a window to attempt for breeding pigs for resistance towards ETEC mediated diarrhoea using putative candidate genes as markers for indirect selection. However, exact causative mutations responsible for genetic variation in susceptibility to ETEC-F4 are unknown (Schroyen et al, 2012), MUC13 have been proposed to be a putative candidate gene that has been extensively studied for its role in imparting resistance to piglet diarrhoea in piglets. Zhang et al (2008) found out that the MUC13 is in strong linkage disequilibrium with enterotoxigenic E.coli (ETEC) F4ab/ac receptor locus.…”
Section: Introductionmentioning
confidence: 99%